Ionic‐Liquid‐Assisted Microwave Synthesis of Solid Solutions of Sr1−xBaxSnO3 Perovskite for Photocatalytic Applications. Issue 17 (17th July 2017) - Alammar, Tarek; Slowing, Igor I.; Anderegg, Jim; Mudring, Anja‐Verena
Abstract: Nanocrystalline Sr1− x Ba x SnO3 ( x =0, 0.2, 0.4, 0.8, 1) perovskite photocatalysts were prepared by microwave synthesis in an ionic liquid (IL) and subsequent heat‐treatment. The influence of the Sr/Ba substitution on the structure, crystallization, morphology, and photocatalytic efficiency was investigated and the samples were fully characterized. On the basis of X‐ray diffraction results, as the Ba content in the SrSnO3 lattice increases, a symmetry increase was observed from the orthorhombic perovskite structure for SrSnO3 to the cubic BaSnO3 structure. The analysis of the sample morphology by SEM reveals that the Sr1− x Ba x SnO3 samples favor the formation of nanorods (500 nm–5 μm in diameter and several micrometers long). The photophysical properties were examined by UV/Vis diffuse reflectance spectroscopy. The band gap decreases from 3.85 to 3.19 eV with increasing Ba 2+ content. Furthermore, the photocatalytic properties were evaluated for the hydroxylation of terephthalic acid (TA). The order of the activities for TA hydroxylation was Sr0.8 Ba0.2 SnO3 >SrSnO3 >BaSnO3 >Sr0.6 Ba0.4 SnO3 >Sr0.2 Ba0.8 SnO3 . The highest photocatalytic activity was observed for Sr0.8 Ba0.2 SnO3, and this can be attributed to the synergistic impacts of the modification of the crystal structure and morphology, the relatively large surface area associated with the small crystallite size, and the suitable band gap and band‐edge position. Abstract : Raising the barium : A sustainable procedure for the preparation of Sr1− x Ba x SnO3 perovskites for photo‐catalytic applications through microwave irradiation in an ionic liquid as a microwave absorbing agent, green solvent, and capping agent is presented.